Aspectos fonéticos perceptivos auditivos da qualidade vocal de teleoperadores de emergência antes e após jornada de trabalho - Medeiros, Camila Macêdo Araújo de (2019)
The objective of this study is to compare voice quality settings and features of voice dynamics of a group of call operators from an emergency call center in João Pessoa – Paraíba, before and after a working day. The analysis was based on The Phonetic Description of Voice Quality (LAVER, 1980), that allows the investigation of the voice quality from the analysis of the settings performed by the vocal apparatus during speech. An auditory-perceptual analysis was conducted using the VPAS-PB, with speech samples (from three carrier sentences) gathered before and after a working day. 23 individuals participated in this study (13 female and 10 male), who were 39.83 years old in average, and with a length of service of 6.87 years in average. An inferential analysis was conducted using the McNemar and Wilcoxon tests, by means of R (R CORE TEAM, 2019), at the significance level of 5%. The most frequent settings before a working day were: tense vocal tract (n = 13), tense larynx (n = 13), harsh (n = 11), pharyngeal constriction (n = 10), decreased pitch variability (n = 10) and minimized pitch range (n = 9). After a working day, the most frequent settings were: tense larynx (n = 19), harsh (n = 17), tense vocal tract (n = 11), raised larynx (n = 10), decreased pitch variability (n = 12), and inadequate respiratory support (n = 11). The tense larynx (p = 0.041) and hoarseness (p = 0.041) settings were considered statistically significant when data from before and after a working day were compared. After a working day, the degree of the following settings increased: minimized labial range (p = 0.020), tense larynx (p = 0.003), hoarseness (p = 0.008), fast elocution rate (p = 0.035) and inadequate respiratory support (p = 0.010). In general, it was possible to identify the presence of settings in the vocal tract of the emergency call operators that indicate a vocal overload. After a working day, the subjects showed settings that cause vocal overload, since they reduce the dimension of the supraglottic cavities and the extension of the vocal tract. In this study, the auditory-perceptual analysis using VPAS-PB contributed to the understanding of the vocal pattern of the call operators from an emergency call center. Thus, it was possible to highlight the vocal overload that this population is exposed to, what indicates a risk of developing a voice disorder.